Funding Research Certification Programs in the Sphere of Tourism on the Example of Developed and Developing Countries - AKBULAEV, Nurkhodzha (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022, 2022)
Tourism is a dynamically developing branch of the national economy of both developed and developing countries, which, accordingly, have the necessary potential of recreational resources. The purpose of standardization in the field of tourist services is to increase the level of safety of a tourist product or a separate tourist service, to ensure the declared level of quality, as well as to protect the interests of consumers of tourist services from unfair competition in the market. Compliance of tourist services sold to the consumer with the requirements of legislative and regulatory documents, established standards is confirmed by a certificate issued by an authorized certification body. One of the effective methods of branding of the territory (region) is outsourcing of foreign services of certification, standardization and Metrology, including in the field of tourism. In this regard, the issues of financing of certification, standardization and Metrology processes in the field of tourism are particularly relevant. It is worth noting that in the situation of developing countries, where the national system of voluntary certification is not always trusted by foreign investors, the most relevant analysis of the best practices of developed countries and the outsourcing of relevant services from specialized transnational corporations. In this study, we analyzed the certification programs in the field of tourism and their financing models, as well as clarified the role of outsourcing of foreign certification services, standardization and Metrology in the field of branding of the territory and developed recommendations for optimizing financial flows. The results of the study will be useful to the General scientific community around the world.